Decentralization and its Impact on Governance and Political Accountability in Madagascar - Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire; Bien-Aimé, Whega Danitsaike; Augustin, Ravaoarisoa Simonette (Journal of Administration, Governance, and Political Issues, 2025)
This study examines the impact of decentralization on governance and political accountability in Madagascar, where reforms aim to bring government closer to citizens and enhance service delivery, participation, and accountability. Despite these intentions, concerns persist about the practical effectiveness of decentralization at the local level. Employing a qualitative approach, the study draws on in-depth interviews with 40 participants, comprising 20 citizens from various regions and 20 political actors, including mayors, parliamentary assistants, and local officials. These perspectives reveal that decentralization has improved physical access to government structures and opened limited avenues for citizen engagement. However, its implementation remains weak and uneven. Key challenges include limited financial and technical resources, low administrative capacity, and ineffective accountability mechanisms. In many instances, responsibilities have been devolved without adequate support, leading to frustration among both citizens and local authorities. The findings suggest that meaningful decentralization requires not only the transfer of authority but also robust institutional frameworks, sustained capacity-building, and inclusive governance practices. By highlighting the lived realities of both citizens and officials, this study provides practical insights for policymakers and development partners seeking to enhance the effectiveness of local governance and strengthen democratic accountability in Madagascar.